Inclusion of dietary lysine on growth, carcass yields and serum biochemical indices in broiler chickens (Bangladesh Journal of Animal Science, 2024)
The experiment was conducted to compare the effect of different sources of lysine on growth performance, carcass yields and serum biochemical parameters in broiler. A total of 400 Arbor Acres straight run chicks were randomly assigned into 4 different treatment groups for five weeks. The treatment groups were; T1 (100% Ajinomoto lysine), T2 (100% CJ lysine), T3(100% Natural lysine) and T4(50% Ajinomoto + 50% Natural lysine). Each treatment consisted of four replicates and of each 25 chicks. Throughout the experiment body weight, body weight gain, feed intake and feed conversion ratio were recorded as growth performance. Carcass characteristics and blood biochemical profile were also taken after the end of feeding trial. The supplementation of different sources of lysine with feed had significant (P